4193delC, a common mutation causing Wilson's disease in Saudi Arabia: rapid molecular screening of patients and carriers. Issue 5 (26th September 2003) - Majumdar, R; Al Jumah, M; Fraser, M
Abstract : Background: In patients with Wilson's disease (WD), an autosomal recessive disorder, toxic accumulation of copper results in fatal liver disease and irreversible neuronal degeneration. ATP7B, the gene mutated in WD, contains 21 exons and encodes a copper transporting ATPase. A novel disease causing mutation (4193delC) in exon 21 of the ATP7B gene has previously been detected by heteroduplex analysis and DNA sequencing. Aims: To screen for the above mutation in patients with WD and carriers using an amplification refractory mutation system (ARMS). Methods: ARMS was used to screen for the 4193delC mutation in 30 patients with WD and their relatives. Results: A homozygous mutation was detected in 16 of 30 patients with WD. Conclusions: This polymerase chain reaction based method, which has been known for years, is a simple, inexpensive, and rapid method for screening common and specific mutations in patients with WD and carriers.